Pengaruh Abu Ampas Aren Terhadap Kuat Tekan Sebagai Bahan Tambah Semen Pada Beton Normal - Latif Gunawan; Dendi Yogaswara; Ismi Purnamasari (Jurnal Konstruksi, 2025)
Concrete is a material that has been widely used to build various types of buildings. To produce concrete that meets the requirements, research and quality of the mixed materials used are needed. Additional materials for concrete are a mixture of basic materials such as water, cement, fine aggregate, and coarse aggregate, and ash. In previous studies, the silica content of onggok starch ash or aren pulp ash was 27.89%. This study aims to determine the compressive strength value of concrete with the addition of aren pulp ash to the weight of cement at the age of 28 days. This study was conducted in the laboratory using a quantitative method with data taken based on the results of research in the laboratory. Arenga pulp ash was added as an additional cement material at levels of 2.5%, 5%, and 7.5% to the compressive strength of concrete. The results of this study for the planned Bet-on met the requirements of 20 MPa with a compressive strength of 21.81 MPa; a mixture variation of 2.5% was 16.37 MPa, 5% was 15.66 MPa, and 7.5% was 15.56 MPa. Based on the results of the concrete compressive strength test with the addition of palm waste ash to the concrete mixture, there was a decrease in the compressive strength of the concrete, so the addition of palm waste ash cannot be used for the concrete mixture because it causes a decrease in the compressive strength of the concrete.